Multiple aspects of DNA and RNA : from biophysics to bioinformatics - Chatenay, Didier (Les Houches., 2005)
Dedicated to the multiple aspects, that is, biological, physical and computational of DNA and RNA molecules, this book is divided into three main sections. It is intended to be a reference for advanced graduate students or young researchers to acquire an interdisciplinary understanding of the multiple aspects of DNA and RNA.